An Analysis of Delay in Enforcement of Contractual Judgments as Impediment to Foreign Direct Investments (FDI) in Nigeria - Rabiu, Ahmed (Ahmadu Bello University, 2014)
Foreign Direct Investment (FDI) is about economic prosperity and wealth creation of developing economies, (FDI) brings with it capital, technology, it provides a platform for the creation of jobs and links to the world economy which brings development. The New Partnership for Africa’s Development [NEPAD] asserts that to meet its developmental challenges, Africa will have to rely more on foreign direct investment [FDI] than aid. Given the fact, the aid flows to Africa have significantly declined over the years and that the continent has now to compete with other countries for the same resources needed for development. Therefore, [NEPAD] places greater emphases on the importance of foreign direct investment [FDI] as Africa’s new engine of economic growth, particularly in the manufacturing and agricultural sector, as opposed to the oil and gas and other natural resources. However, the contribution firms, and foreign direct investment [FDI] make to the society is determined principally by the investment climate. There are many features of a good investment climate, aside of legal framework, provision of security and maintaining infrastructure, which provide the opportunities and incentives for the investment to flow and flourish and create confidence in the mind of the investors, to invest productively, and they include strong and vibrant contract enforcement. Delays or uncertainties in the enforcement of contractual rights erode the value of property rights and diminish the opportunities and incentives to invest. Therefore, the process of seeking redress through the normal court system is too protracted and unsatisfactory to continue to serve as primary recourse option of executives and potential investors, and this also explain the slow of improvement in FDI in the manufacturing and agricultural sector inflow to Nigeria. There are additional reasons for all these difficulties and hurdles that constitute a clog to an efficient contractual enforcement. The legal system that made judges of regular courts to also handle election petitions and other ad-hoc assignments to the detriment of the regular pending commercial cases before the courts. Secondly, there currently distinct rules for each state of the Federation and there number of civil procedure rules required to be complied with to move cases through the system from filing to judgment enforcement. This has created additional and unnecessary procedures that elongate the process of contract enforcement. Thirdly, despite these enormous powers of the Sheriff and bailiffs in the process of trials and enforcement of contractual judgments, in Nigeria majority of the bailiffs in all our courts including the courts of records are either retired police or military officers with no formal training on their powers and obligations in accordance with the provision of the law.The dissertation mainly recommended the creation of Commercial courts or Commercial divisions throughout the federation to handle contractual and commercial cases; secondly, Secondly, it is recommended for the unification and adoption of a single the civil procedure rules throughout the country. Lastly to institutionalize the training and retraining of sheriffs and court bailiffs on the provisions of the rules as it relates their functions of giving effect to court orders and judgment.These would go a long way in providing an effective and speedy movement of civil cases through the system of trial and subsequent enforcement in our courts, which may further create confidence and improve the investment climate for the inflow of the Foreign Direct Investment (FDI) in to Nigeria.
Keywords: Contract; Enforcement; FDI; Foreign direct investment; Impediment; Investments; Judgments; Nigeria

The effects of the South African anti-dumping and competition measures upon foreign direct investment - Sibanda, Omphemetse S. (Journal of Business and Retail Management Research, 2014)
Since the dawn of democracy South Africa has embarked in a process of dismantling protectionist business and trade policies, and made the country’s stream of commerce one of the preferred globally. The country’s sound competition and trade policies, natural resource endowments, market size and regional influence, attracted foreign businesss and foreign direct invetsment (FDI). Equally the country has been under pressure to protect the domestic industries from injurious competition and business, through sector specific laws, anti-dumping and countervailing duties laws, investment and competition regime. The concern has been the likilelihood of the introduction of trade and competition barriers, and the allienation of FDI. This paper critically examines the impact the country’s antidumping and competition law and practice upon foreign direct investment. Domestic industries have never been shy to file anti-dumping and anti-competition suits against foreign companies, sometimes even when there might be a public outcry. Relevant examples of these suits include the famous Wal-Mart anti-competition case, and recently the Brazilian frozen fowl meat anti-dumping case.
Keywords: Anti-Dumping; Competition; Consumers; Divestment; Domestic Industry; Investments; Protection; Tariffs

Reconciling international investment law and sustainable development with respect to host state's right to regulate : the legal impact of sustainable development objective on indirect expropriation standard and its legitimate expectations sub-element - Dubava, Ilze (European University Institute, 2014)
This thesis seeks to determine whether the evolution of international law has allowed for the concept of cultural genocide to be addressed in spite of its non-codification. It firstly provides an assessment of the evolution of the concept of cultural genocide, from a technique to a process of genocide, also known as 'ethnocide'. Acknowledging that the codification of the concept is unlikely in the future, it therefore undertakes a study of the evolution of international law with regard to the main components of the concept, namely genocide, culture and group. The evolution of the legal concept of 'genocide' raises the question of the interpretation of the international definition of genocide, which is enshrined in the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, so as to encompass instances of cultural destruction. The state of international and domestic judicial practice illustrates the limits of an evolutionary interpretation. In contrast, international law has evolved considerably in relation to the protection of some groups and their culture, so that customary international law, and especially international human rights law, may be deemed to prohibit group cultural destruction and consequently entail State responsibility. The thesis argues that this evolution could ground the articulation of an international law-based approach to the concept of cultural genocide both by allowing for its criminalisation through the crime against humanity of persecution and by providing tools for a stronger framework of State responsibility, especially in the context of genocide prevention. Furthermore, this approach would give rise to the possibility of further conceptualising reparation for the intended cultural damage. Against this background, the thesis firstly draws conclusions as to the irrelevance of enclosing the debate exclusively at the level of the genocide legal framework and, secondly, as to the relevance of cultural genocide as a 'paralegal concept', an understanding which would drive the interpretation of international legal norms, especially in cases involving indigenous peoples' cultural harm.
Keywords: Economic aspects; Economic development; Foreign investment; International Law; Investments